Akibat Hukum terhadap Kejahatan Perpajakan dengan Faktur Pajak Fiktif - Subroto, Edwin Sulasdjono; Sidarta, Dudik Djaja; Soekorini, Noenik (Penerbit Goodwood, 2024)
Purpose: This study analyzes the legal consequences of tax crimes with fictitious tax invoices by corporations and judges’ Considerations in Imposing Criminal Sanctions on Perpetrators of the Criminal Act of Using Fictitious Tax Invoices by corporations in Decision Number 523 / Pid.Sus / 2021 / PN Cikarang, Decisito analyze27 / Pid.Sus / 2021 / PN Jkt.Utr, and Decision Number 926 / Pid.Sus / 2019 / PN Jkt.Utr. Research Methodology: The type of research is normative juridical with a research approach, namely, the statute and conceptual approaches. The legal materials for this research include Primary Legal Materials, namely Law No. 7 of 2021 and Law No. 28 of 2007, while Secondary Legal Materials are information from the media and the literature. Collection of legal research materials through library research, legal material analysis techniques, and descriptive analysis. Results: The results of this study prove that the legal consequences of tax crimes with fictitious tax invoices by corporations can be subject to criminal penalties in accordance with Article 39A of Law No. 7 of 2021, with a minimum imprisonment of two years and a maximum of six years and a fine of at least two times the amount of tax in the tax invoice, proof of tax collection, proof of tax deductions, and/or proof of tax payments, and a maximum of six times. The judge’s Consideration in Imposing Criminal Sanctions on Perpetrators of the Criminal Act of Using Fictitious Tax Invoices by Corporations in the Decision is in accordance with Article 39A of Law No. 7 of 2021. Limitations: This study only focuses on the Legal Consequences of Tax Crimes with Fictitious Tax Invoices in the Decision Number 523 / Pid.Sus / 2021 / PN Cikarang, Decision Number 1227 / Pid.Sus / 2021 / PN Jkt.Utr and Decision Number 926 / Pid.Sus / 2019 / PN Jkt.Utr. Contributions: This research can be a means of education in analyzing the legal consequences of tax crimes with fictitious tax invoices in the decisions of Decision Number 523 / Pid.Sus / 2021 / PN Cikarang, Decision Number 1227 / Pid.Sus / 2021 / PN Jkt.Utr and Decision Number 926 / Pid.Sus / 2019 / PN Jkt.Utr.